SUCCESS OF INTRAVITREAL RANIBIZUMAB IN ACUTE CENTRAL SEROUS CHORIORETINOPATHY - Chalid Kurniawan; Arief Kartasasmita (Indonesian Vitreoretinal Society, 2020)
Introduction: Central serous chorioretinopathy (CSC) manifests as neurosensory detachment of the macula and observation has been considered as an appropriate first-line approach. Active treatment is required to prevent recurrences or chronic type. This study aim to evaluate the effectiveness of intravitreal ranibizumab injection (IVRI) for acute CSC. Methods: A single-center retrospective descriptive study. Five files of the patients who had the diagnosis of CSC then treated with IVRI between 2018 and 2019 have been investigated. IVRI were given once every 4 weeks until sub-retinal fluid resolved. Demographic details, best-corrected visual acuity (BCVA), and central macular thickness (CMT) were studied before and after treatment. Results: The mean age of the patients was 57 years (SD= 10.5 years) mostly female (3 patients). The mean duration before treatment was 3.8 weeks (SD= 1.4 weeks). The mean number of IVRI was 1.4 (SD= 0.5). The mean CMT before IVRI was 436.4 μm (SD= 109.1) and decreased to 243 μm (SD= 38.3) at the last visit. The mean BCVA before IVRI was 0.56 logMAR (SD= 0.37) and improved to 0.22 logMAR (SD= 0.29) Conclusion: IVRI appeared to be effective treatment for acute CSC. The mean CMT decreased and BCVA improved after therapy.